Given f(x) = 3x + 5 and g(x) = x² - x + 7, which of the following is an expression for f(g(x))?
F.) 3x² - 3x + 26 G.) 3x² - 3x + 12 H.) x² - x + 12 J.) 9x² + 25x + 27 K.) 3x² + 21
0 Comments
Let the function g be defined by g(x) = 3(x² - 2). When g(x) = 69, what is a possible value of 2x - 3?
F.) -7 G.) -5 H.) 2 J.) 5 K.) 7
What are the solutions for the equation 3x² - 5x + 2 = 0?
F.) x = -1 or -3/2 G.) x = 1 or 2/3 H.) x = -5 or 2/3 J.) x = 2/5 or 1 K.) x = -1 or 3/2
A company earned a profit of $8.0 million each year for 3 consecutive years. For each of the next 2 years the company earned a profit of $9.0 million. For this 5-year period, what was the company's average yearly profit, in millions of dollars?
A.) 8.2 B.) 8.25 C.) 8.4 D.) 8.5 E.) 8.6 |
Latest Videos## Archives
June 2021
ACT is a registered trademark of ACT, Inc. SAT is a registered trademark of the College Board. ACT and SAT are not affiliated with this site. |